PENGARUH PERENCANAAN PAJAK DAN ASET PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (2015-2017) - SARAGIH, AFNI ELIANA; MANULLANG, AGUSTINA RAHAYU (UNIKA Santo Thomas, 2022)
This study aims to determine and empirically prove the effect of tax planning and deferred tax assets on earnings management. The population in this study are all financial statements of infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange in 2015-2017. The sample in this study was obtained by purposive sampling, with a total sample of 17 companies. Data collection techniques using documentation techniques. The data analysis technique used is multiple linear regression and hypothesis testing using t test and f test with a significance level of 5%. The results of this study indicate that the partial test (t test): (1) tax planning has no significant positive effect on earnings management, this is evidenced by the t test where tax planning has a t count < t table (0.050 < 1.67528) with significant level of 0.960 > 0.05. Which means that the tax planning carried out does not guarantee the implementation of earnings management by the Indonesia Stock Exchange company. (2) deferred tax assets have a negative and significant effect on earnings management. This is evidenced by the t test where the deferred tax assets have a t value < t table (-2.737 < 1.67528) with a significant level of 0.009 < 0.05. Which means that the amount of deferred tax assets affects earnings management in infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange. The results of the simultaneous test (F test) of tax planning and deferred tax assets are positive and have a significant effect on earnings management.